2017
DOI: 10.1002/jaal.701
|View full text |Cite
|
Sign up to set email alerts
|

Building Background Knowledge Through Reading: Rethinking Text Sets

Abstract: The quad text set framework can assist content teachers in building students' background knowledge, increasing their reading volume, and incorporating complex texts into instruction.A call for continued efforts to improve literacy outcomes for adolescents is standard fare, but exactly what adolescents should read, how much, and how are less clear. As former middle and high school teachers and current university-based literacy researchers, we take the stance that increasing the amount of challenging texts that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…For example, Adam wanted to try using Cornell Notes (Vacca et al, 2017) again because our evidence suggested that this note-taking system helped students comprehend the text. However, he wanted students to develop a stronger awareness of the issues, so he created a text set designed to support understanding of a target text (Lupo, Strong, Lewis, Walpole, & McKenna, 2018) and adapted Cornell Notes to include the following sections: big idea, supporting details, and point of view. In Figure 3, the same student from the Cornell Notes example in Figure 2 analyzed three articles related to tensions around the Dakota Access Pipeline.…”
Section: Feature Articlementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Adam wanted to try using Cornell Notes (Vacca et al, 2017) again because our evidence suggested that this note-taking system helped students comprehend the text. However, he wanted students to develop a stronger awareness of the issues, so he created a text set designed to support understanding of a target text (Lupo, Strong, Lewis, Walpole, & McKenna, 2018) and adapted Cornell Notes to include the following sections: big idea, supporting details, and point of view. In Figure 3, the same student from the Cornell Notes example in Figure 2 analyzed three articles related to tensions around the Dakota Access Pipeline.…”
Section: Feature Articlementioning
confidence: 99%
“…. Gather materials: Create a quad text set about the topic by identifying a target text and building support with three other texts, which may include video and popular media(Lupo et al, 2018).4. Restate one's position:Ask students to state their current position on the issue in light of new information.5.…”
mentioning
confidence: 99%
“… Listen‐read‐discuss (Manzo & Casale, ): This process begins with the teacher selecting a well‐written portion of the text to be covered and presenting critical terms and ideas to the students through short summaries or discussions prior to reading. This is followed by the students independently reading the selection and having a discussion that focuses on both clarifying what was read and raising broader or more complex issues connected to the text. Laddering texts or the use of text sets (e.g., Lupo, Strong, Lewis, Walpole, & McKenna, ): By providing a series of texts with varying difficulty levels, from easier to more challenging, on the same subject, learners are able to build their background knowledge through their reading. Both concepts and vocabulary are likely to be repeated across these selections, helping increase both the breadth and the depth of students’ knowledge of the subject at hand. Scaffolded silent reading (Reutzel, Jones, Fawson, & Smith, ): This strategy is based on the understanding that if students are to become skilled readers across a range of genres, they need to read texts in these genres; to accomplish this, students are expected to select texts using a genre wheel rather than simply choose one type of text, such as dystopian fiction, that they are already comfortable reading.…”
Section: Thinking About Reading Widelymentioning
confidence: 99%
“…■ Laddering texts or the use of text sets (e.g., Lupo, Strong, Lewis, Walpole, & McKenna, 2018): By providing a series of texts with varying difficulty levels, from easier to more challenging, on the same subject, learners are able to build their background knowledge through their reading. Both concepts and vocabulary are likely to be repeated across these selections, helping increase both the breadth and the depth of students' knowledge of the subject at hand.…”
Section: Commentarymentioning
confidence: 99%
“…Lewis, Walpole, and McKenna () developed a quad text set consisting of a core text, an additional informational text, a visual text, and a related literary text. Classroom teachers need to consider both modalities and genres when designing and using multiple texts (Lupo et al, ).…”
Section: One Classroom Example: Ms Nallis's 10th‐grade Health Classmentioning
confidence: 99%